HUBUNGAN KANDUNGAN NITRAT TERHADAP PERTUMBUHAN LAMUN (Enhalus acoroides) DI PESISIR PANTAI NEGERI SULI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Risaldi Abidin; John F Rehena (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: Seagrass (Enhalus acoroides) is a type of seagrass that has the largest size, leaf strands can reach sizes> 1m. This type grows in shallow waters to a depth of 4 meters, on the basis of sand, mud sand or mud. The purpose of this study was to determine the relationship of nitrate content to the growth of seagrass (Enhalus acoroides) on the coast of Suli Village Salahutu District, Central Maluku Regency. Method: The type of research used in this study was descriptive to determine the relationship of nitrate content to growth of seagrass Enhalus acoroides on the coast of Suli State Salahutu District, Central Maluku Regency. The study was conducted on February 1-15, 2018. Results: This study showed that each transect had different growths of seagrass length, namely on transect 1, seagrass growth, reaching an average of 1.05, transect 2 averaging 1.01, while on transect 3 seagrass growth reached 1 average. , 35. Transect 3 has a greater growth rate than transect 1 and transect 2 while transect 2 has a lower growth rate than transect 1 and transect 3, while the results of the measurement of the average nitrate level on all transects are the same namely at transect 1 of 0.020 mg / l, transect 2 is 0.010 mg / l and transect 3 is 0.210 mg / l. Conclusion: Oligtrofic waters have nitrate levels between 0-5 mg / l, mesotrophic waters have nitrate levels between 1-5 mg / l, and eutrophic waters have nitrate levels ranging from 5-50 mg / l.